Gossypiboma after Breast Augmentation. (14th February 2013) - Lundin, Kira; Allen, Julie E.; Birk-Soerensen, Lene
Abstract : A 39-year-old woman was referred for removal of cosmetic breast implants and related siliconoma. After an exchange of breast implants at a private clinic a year previously, she had asymmetry of the right breast, persistent pain, and a generally unacceptable cosmetic result. An MRI had shown a well-defined area with spots of silicone-like material at the upper pole of the right breast. Surgical removal of presumed silicone-imbibed breast tissue was undertaken, and surprisingly a gossypiboma was found in its place, which had not been identified on the MRI. Gossypiboma is the condition of an accidentally retained surgical sponge. This complication is also known as a textiloma, gauzoma, or muslinoma and is well described in other surgical specialties. However, it is extremely rare after plastic surgery, and this case illustrates the need for continued attention to the surgical count of sponges and instruments.